Analisis Tingkat Kepuasan Pengguna Aplikasi Competence Development Center (CDC) pada Lembaga Pendidikan Pengembangan Profesi Indonesia (LP3I) Menggunakan Metode End-User Computing Satisfaction (EUSC) - Tanoga, Ruhdiara; Ahmad, Lukman; Akbar, Rizaldi (Jurnal Ilmu Komputer dan Teknologi Informasi, 2025)
This study aims to analyze user satisfaction with the Competence Development Center (CDC) application developed by LP3I using the End User Computing Satisfaction (EUSC) method. The EUSC method is applied to evaluate various aspects of user satisfaction, including usability, reliability, feature availability, and the overall user experience with the application. The approach used in this study is quantitative, with data collected through online questionnaires distributed to active users of the CDC LP3I application. Respondents were purposively selected based on specific criteria, such as the frequency of application use and the level of engagement with the available features. The collected data were analyzed using descriptive and inferential statistical techniques to identify the factors influencing user satisfaction. The results of the study indicate that most users are satisfied with the CDC LP3I application, particularly in terms of usability and feature availability. However, some areas require improvement, such as system reliability and support service responsiveness. These findings provide valuable insights for the developers of the CDC LP3I application to enhance quality and user satisfaction. This study also contributes to the literature on evaluating user satisfaction with mobile applications in the fields of education and professional development. Furthermore, the findings can serve as a foundation for further development of the CDC LP3I application and as a reference for other educational institutions planning to implement similar technology.